STRUCTURAL AND DIMENSIONAL FEATURES OF JOINT-INTERNAL LIGAMENTS IN INDUCED OSTEOARTHRITIS MODELS - Eshonkulova Bakhriniso Dustmuradovna,; Rasulova Shaxzodaxon Xaydarbek qizi, (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
Osteoarthritis (OA) represents one of the most pressing global health challenges, affecting over 500 million people worldwide and projected to double by 2050 due to aging populations and rising obesity rates. This thesis investigates the morphological and morphometric alterations in intra-articular ligaments, such as the anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL), in experimental OA models using animal subjects. Through detailed histological and quantitative analyses, we reveal progressive ligament degradation, including fiber disorganization, increased thickness variability, and reduced tensile strength, which correlate with cartilage erosion and joint instability. These findings underscore the critical role of ligaments in OA pathogenesis, offering novel insights for early diagnostic biomarkers and targeted therapies, thereby addressing an urgent need in regenerative medicine amid escalating socioeconomic burdens of chronic joint diseases.